Ecological urbanism in the tropics studies on the sustainable dimensions of Malay traditional urban centers - Jahn Kassim, Puteri Shireen; Ibrahim, Illyani; Harun, Nor Zalina; Kamaruddin, Kamariah (Science Publishing Corporation Inc., 2018)
Many of the present eco-cities are designed and planned with an emphasis on high technology and infrastructure yet the meaning of sustainability itself implies a balance between past and present. Past urban configurations that rise from earlier traditional socio-cultural structures reflect sustainable principles localised to climate and ecology. The aim of this study is to reconstruct urban morphologies be-fore the advent of the automobile in order to analyse and characterise urban forms that are aligned with ecological criteria such as walk-ability, permeability and shade. Three traditional urban center or ‘cores’ in tropical Malaysia which had reigned during the early colo-nial era yet still related sultanate-based polities are mapped in terms of morphologies and these urban ‘core’ configurations were esti-mated and composed according to historical documents and evidences . These urban patterns are then discussed with regards to the present principles and criteria of green urbanism. The reconstructed and mapped urban cores are discussed in relation to green urban-ism principles and criteria, namely, based on global sustainable standards namely the LEED ND (Leadership in Energy and Environ-mental Design) version 4 neighbourhood rating system. The findings from this study suggest the contextualization of sustainable criteria according to climate and postulate the differences between traditional urban morphologies that can further regionalism principles of current green urbanism and further contextualise key principles in international standards on urbanism.